O pensamiento de Ignacio Rangel - CAMPOS, Domar; MAMIGONIAN, Armen; MERCADANTE, Paulo; MONTEIRO DE CASTRO, Marcio Henrique; PAIM, Gilberto; PIZZO, María do Rosario (UNIVERSIDAD FEDERAL DE SANTA CATALINA, 1997)
Contiene: 1ºSimposio Nacional.Florianópolis, 1994.Otros autores: WANICK RIBEIRO, Sylvio; REGO, José Marcio